Heavy metals (mercury, arsenic, cadmium, plumbum) in selected marine fish and shellfish along the Straits of Malacca - Mohamad, Alina; Azlan, Azrina; Abd. Shukor, Mohd Yunus; S., Mohd Zakiuddin; Halmi, Mohd Izuan Effendi; Razman, Muhammad Rizal (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Level of heavy metals in marine ecosystem has been intensively studied during recent years as these hazardous substances could be accumulated in the biota. Generally, the presence of contaminants in fish is a result of human activities such as industrial and agricultural wastes. In this study, the marine fish and shellfish from the Straits of Malacca were analyzed using Inductively Coupled Plasma Optical Emission Spectrophotometer (ICP-OES) and Flow Injection Mercury System (FIMS) for Cd, As and Pb and Hg, respectively. The Straits of Malacca is one of the busiest shipping routes in the world that make the level of heavy metals potentially high besides the various industrial activities along the west region of Peninsular Malaysia. The range of heavy metals in samples were 1.0-3-6.5-3 μg/ g wet sample for Hg, 0.5-2-47-2 μg/ g wet sample for Cd, 0.01-0.39 μg/ g wet sample for Pb and 0.14-6.57 μg/ g wet sample for As. Most part of the values was below the permitted limit set by FAO/WHO 2004 as well as Food Act 1983 and Food Regulations 1985. Therefore it can be generalized that fish and shellfish from the Straits of Malacca are safe to consume in terms of these heavy metals concentration and do not constitute a risk for human health.